Phase Separation of Li2S/S at Nanoscale during Electrochemical Lithiation of the Solid‐State Lithium–Sulfur Battery Using In Situ TEM. Issue 20 (26th July 2016) - Yang, Zhenzhong; Zhu, Zhiyong; Ma, Jie; Xiao, Dongdong; Kui, Xian; Yao, Yuan; Yu, Richeng; Wei, Xiao; Gu, Lin; Hu, Yong‐Sheng; Li, Hong; Zhang, Xixiang
Abstract : S/Li2 S phase separation at nanoscale is observed for the first time in the solid‐state Li–S battery by using in situ transmission electron microscopy. This nanophase separation not only reduces the diffusion distance but also provides the S/Li2 S interfaces network, which is favorable for electron and Li + ion transportation during the lithiation process.